2018
DOI: 10.1103/physrevb.98.245123
|View full text |Cite
|
Sign up to set email alerts
|

Spin-orbit coupling driven insulating state in hexagonal iridates Sr3MIrO6 ( M=Sr

Abstract: The spin-orbit coupling (SOC) interactions, electron correlation effects and Hund coupling cooperate and compete with each other, leading to novel properties, quantum phase and non-trivial topological electronic behavior in iridium oxides. Because of the well separated IrO 6 octahedra approaching cubic crystal-field limit, the hexagonal iridates Sr 3 MIrO 6 (M = Sr, Na and Li) serves as a canonical model system to investigate the underlying physical properties that arises from the novel J eff state. Based on d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 69 publications
4
11
0
Order By: Relevance
“…However, the experimentally obtained value is close to the reported magnetic moments 3.6µ B per formula unit for Ba 3 NaIr 2 O 9 and 3.93µ B per formula unit for Ba 3 LiIr 2 O 9 , both having Ir in a similar 5.5 charge state [21]. Such reduction in moment is a peculiar feature seen in iridates and has been reported for a wide range of iridium based oxides [6,[22][23][24].…”
Section: Resultssupporting
confidence: 87%
“…However, the experimentally obtained value is close to the reported magnetic moments 3.6µ B per formula unit for Ba 3 NaIr 2 O 9 and 3.93µ B per formula unit for Ba 3 LiIr 2 O 9 , both having Ir in a similar 5.5 charge state [21]. Such reduction in moment is a peculiar feature seen in iridates and has been reported for a wide range of iridium based oxides [6,[22][23][24].…”
Section: Resultssupporting
confidence: 87%
“…Finding this optical mode by increasing the experimental energy range may help to clarify the microscopic understanding of the ground state of Ca 2 RuO 4 . Furthermore, our findings may be of direct relevance for one-dimensional t 4 2g materials, such as OsCl 4 [82] and Sr 3 NaIrO 6 [84]. Especially the later is of interest, because a recent experimental study [83] showed the presence of short-range antiferromagnetic correlations and gapless spin excitations resembling the antiferromagnetic excitonic condensate phase.…”
Section: Discussionmentioning
confidence: 72%
“…For d 4 systems with nominally n 1 =0, the relative energy shift increases to U − 3J H . This enhancement of the spin-orbit gap renormalization is seen in recent DFT study of the hexagonal iridates Sr 3 LiIrO 6 and Sr IrO 6 with Ir 5+ (5d 4 ) and Ir 4+ (5d 5 ) ions, respectively 25.…”
mentioning
confidence: 53%